Promising Role of Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography in Human Immunodeficiency Virus Associated Non-Hodgkin′s Lymphoma - Boom Kung (World Journal of Nuclear Medicine, 2015)
This case report explores the potential role of FDG PET/CT in HIV -associated systemic non-Hodgkin′s lymphoma (HIV-NHLs). In our locality, there are a cumulative total of 5523 reported HIV infections cases since 1984. We reported a case of HIV-related Burkitt′s lymphoma (BL) and a case of diffuse large B-cell lymphoma (DLBCL) that underwent PET/CT examination in our PET centre. In HIV-NHLs patients, we must be reminded that not all hypermetabolic foci represent lymphomatous lesions. There is a close correlation between the pattern of lymphoid tissue activation in FDG PET/CT and HIV progression in patients without HIV-related malignancy. The unique patterns of lymphoid tissue activation observed in HIV-infected patients have great clinical implications. Secondly, HIV-infected patients are prone to suffer from opportunistic infections due to immunosuppression, particularly in those with high levels of HIV viral loads. FDG PET/CT cannot reliably differentiate metabolic active lymphoma from other benign diseases such as inflammation in the context of low CD4 count and high viral loads. In those cases, benign markedly hypermetabolic foci can be erroneously interpreted as lymphoma, particularly in those normal-sized lymph nodes. Furthermore, FDG PET/CT may be useful for assessing the efficacy of HAART in suppressing HIV replication and detecting its complication such as lipodystrophy. FDG PET/CT may play a potential useful role in staging and management of HIV -associated systemic non-Hodgkin′s lymphoma. Plasma variables such as viral loads and CD4 count must be taken into account during image interpretation. FDG PET/CT as a potential useful tool for diagnosis, treatment response assessment and disease relapse detection in HIV -associated systemic non-Hodgkin′s lymphoma worth to be further explored.